Effects of pivot design on performance of tilting pad journal bearings. (March 2018) - Mehdi, Syed Muntazir; Jang, Kyung Eun; Kim, Tae Ho
Abstract: This paper emphasizes on the effects of pivot flexibility upon the performance of a TPJB by making comparison between two model predictions i.e. (a) model with rigid pivots, and (b) model with soft pivots. The latter one uses Hertzian contact theory for the calculation of the pivot stiffness and couples it with the fluid film hydrodynamics. Presently, finite element method solves pressure distribution which integrates to give fluid film forces and moments. Predicted static and dynamic characteristics using two different models illuminate the dominance of pivot flexibility effects on the performance of the TPJB. In general, soft pivot model predictions are closely predicted when compared to the previously published test data. Highlights: A numerical model has been developed to accurately determine the static and dynamic characteristics of the tilting pad journal bearings with ball-socket and rocker-back pivots. Pivot stiffness has been taken into account and coupled with the fluid film hydrodynamics in a novel way. In order to validate the model, predictions have been compared to the published experimental data. Effects of pivot differential diameter on the static and dynamic performance characteristics have been analyzed and discussed.